Athlete development in ski racing: Perceptions of coaches and parents - Black, D. E.; Holt, N. L. (International Journal of Sports Science and Coaching, 2009)
Federally funded Canadian sports are required to have a Long Term Athlete Development (LTAD) plan. Alpine ski racing developed the Husky Snow Stars (HSS) program to represent the fundamentals and learning to training phases of its overall LTAD plan. The purpose of this study was to evaluate coaches' and parents' perceptions of the implementation of the HSS program at a local level. Using a multiple case-study approach, four Alberta ski racing clubs were purposefully sampled. Data were collected via interviews with eight coaches and 18 parents of ski racers from these clubs. Interviews were transcribed verbatim and subjected to categorical aggregation analysis. Analysis revealed themes related to perceptions of (a) the LTAD plan and its available resources; and (b) assessment of racers' abilities. These findings provide a preliminary assessment of one sport-specific athlete development plan and may inform research into the local level implementation of other sport-specific talent development systems.